A Quantum Chemical of Frontier Molecular Orbit of 4-Amino-Cobalt Phthalocyanine - Xue, Juanqin; Jiang, Meng; Yu, Fanglei; Ma, Jing; Zhao, Xiao (Asian Journal of Chemistry, 2014)
Using the B3LYP/3-21G* of the density functional method,quantum chemical study of the charge, bond length and frontier molecular orbit of CoTAPc (4-amino-cobalt phthalocyanine) has been performed. The results show that the nitrogen atoms have strong nucleophilic activity while the hydrogen atoms have strong electrophilic activity in CoTAPc. Secondly, the two nitrogen atoms of N5 and N10 can form covalent bonds with Co atom and the N13 and N18 can connect with Co atom by the coordinate bonds. Thirdly, the composition of the highest occupied molecular orbital (HOMO) of the CoTAPc mainly comes from the contribution of carbon atoms and nitrogen atoms, while the constitution of the lowest unoccupied molecular orbital (LUMO) mainly comes from the contribution of carbon, nitrogen and cobalt atoms. The oxidation of CoTAPc mainly occurs on the C-C bond while its deoxidization mainly happens on the C-C, C-N and Co-N bonds.